Development of omniphobic behavior in molecular self‐assembled monolayer‐coated nanowire forests. Issue 1 (13th October 2015) - Bong, Jihye; Lee, Jonghun; Lee, Jeongbeom; Ha, Young‐Geun; Ju, Sanghyun
Abstract: The wetting characteristics of self‐assembled monolayers (SAMs) on three different surface structures of thin film, microcone array, and nanowire forest topologies, which were chemically modified using phosphonic acid (HDF‐PA and OD‐PA) and trichlorosilane (HDF‐S), were investigated. The molecular SAM‐coated nanowire forest structures exhibited superhydrophobic properties with contact angles of 150.6°–155.4°, compared with the other structures combined with OD‐PA, HDF‐PA, and HDF‐S SAMs, which displayed contact angles of 99.5°–116.8°. Moreover, the HDF‐PA and HDF‐S SAM‐coated nanowire forest structures showed omniphobic properties for both flat and curved surfaces, irrespective of the substrate form. Four liquid droplets of different viscosities and composition (water, urea solution, oil, and photoresist) slid on the HDF‐PA and HDF‐S SAM‐coated nanowire forest surfaces without leaving any traces. The omniphobic properties of the molecular SAM‐coated nanowire forest structures developed in this study could be used for various applications in which their slippery effect is desirable, such as in medical tubes and the interior of pipes. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 204–210, 2017.